Z33 Contemporary art & design projects collected : red. Monique Verhulst. - Z33, Hasselt; Verhulst, Monique (Hasselt : Z33, 2007)
Amandini, Giovanni ; Andoni, Saed ; Arink, Karin ; Arndt, Olaf ; Asselberghs, Herman ; Atelier van Lieshout ; Bakker, Aldo ; Bakker, Douwe Jan ; Bey, Jürgen ; De Bièvre, Guy ; Bihain, Michaël ; de Boeck, Lieven ; Van Bogaert, Pieter ; Bolink, Merijn ; Boo, Bram ; Branz, Andrea ; Brody, Ondrej ; Brouns, Steven ; Bugaev Afrika, Segei ; Burnett-Rose ; Cobbing, William ; Combinaat ; Coppens, Christophe ; de Decker, Hilde ; Emin, Tracey ; Eventarchitectuur Herman Verkerk ; Farocki, Harun ; Fiveeyes ; Geers, Kendell ; Godard, Jean-Luc ; Gonzalez-Torres, Felix ; Grimonprez, Johan ; Groner, Sagi ; de Gruyter, Voebe ; Heiden, Cécile Van Der ; Hermans, Linde ; Hurkmans, Rini ; Hutten, Richard ; Jongerius, Hella ; Killaars, Fransje ; Köner, Thomas ; de Koning, Krijn ; Körmeling, John ; Kren, Kurt ; Krier, Sébastien ; kuda.org ; Laarman, Joris ; Mackert, Suska ; Marcotti, Saskia ; Margolles, Teresa ; Martens, Renzo ; Meste, Philippe ; Miceli, Alice ; Migone, Christof ; Montens, Cathelijne ; Moonen, Rob ; Van Moorter, Geert ; Mumford, Steve ; Opsomer, Els ; Orta, Lucy ; Otten, Reineke ; OVNI ; Paetau, Kristofer ; Pasolini, Pier Paolo ; Pax, Salam ; Pilotto, Peter ; Rakowitz, Michael ; Ravage ; Rees, David ; Resnais, Alain ; Reuvis, Patrick ; Robijns, Gert ; Rombouts, Guy ; Roosen, Maria ; Rutten, Jeff ; Ruygrok, Marc ; Schmidt, Dierk ; Schuil, Han ; Simons, Raf ; Sokurov, Alexander ; Spinoy, Erik ; Studio Job ; Thaemlitz, Terre ; Ujica, Andrei ; Vandebeek, Roel ; Vandeweerd, Pierre-Yves ; Vangeluwe, Johan ; Verheyden, Michaël ; Vlaemsch () ; De Vree, Marc ; Wapenaar, Dré ; Weiss, Jonathan ; Winter & Hörbelt ; Zoink!
Publicatie n.a.v. de tentoonstellingen'Living in motion', 'Design in bewegin', 'Living in mobile units', 'ZAP33' in Z33 te Hasselt, 28.11.04 - 13.02.05
boek